Interfaith Heirship in Islamic Jurisprudence: Exploring Ijtihad Approaches in Contemporary Legal Reforms - Basarudin; Oyo Sunaryo; Fauzan Ali Rasyid (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study explores the complex issue of interfaith heirship within the framework of Islamic jurisprudence, focusing on contemporary efforts to reinterpret traditional doctrines through ijtihad. Classical Islamic law generally prohibits non-Muslim heirs from inheriting from Muslim relatives, a stance rooted in historical socio-religious contexts. However, in response to evolving pluralistic societies and the growing demand for legal inclusivity, contemporary Muslim scholars and legal reformers have initiated various ijtihad-based approaches to reassess this prohibition. Employing a qualitative normative legal method, this research examines key classical texts, modern fatwas, and statutory reforms in selected Muslim-majority countries. The findings reveal a dynamic spectrum of scholarly opinions, ranging from strict adherence to traditional rulings to more progressive reinterpretations that emphasize maqasid al-shariah (the objectives of Islamic law), particularly justice, family unity, and human dignity. The study concludes that while doctrinal tensions remain, ijtihad presents a legitimate and evolving mechanism to harmonize Islamic inheritance law with contemporary legal and social realities, thereby promoting more inclusive and contextually responsive interpretations.